2022
DOI: 10.4049/jimmunol.2200229
|View full text |Cite
|
Sign up to set email alerts
|

RNF186/EPHB2 Axis Is Essential in Regulating TNF Signaling for Colorectal Tumorigenesis in Colorectal Epithelial Cells

Abstract: The receptor tyrosine kinase EPHB2 (EPH receptor B2) is highly expressed in many human cancer types, especially in gastrointestinal cancers, such as colorectal cancer. Several coding mutations of the EPHB2 gene have been identified in many cancer types, suggesting that EPHB2 plays a critical role in carcinogenesis. However, the exact functional mechanism of EPHB2 in carcinogenesis remains unknown. In this study, we find that EPHB2 is required for TNF-induced signaling activation and proinflammatory cytokine pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…52 Our model is a pregnancy infection model, which was found to have increased plasma inflammatory factors, including TNF-α, after viral infection and it has been reported that TNF-α activates the NF-κB pathway, which affects EphB2 transcription, all three of which can be increased under injury or disease states. 84,85 In Opcml-deficient mice, which exhibit schizophrenic-like behaviors but reduced EphB2 expression, 54 we differ from previous studies, haps because we use a different The pathogenetic mechanisms of different diseases may lead to different changes in EphB2 receptor expression. One limitation of this study is that we did not obtain insight into the mechanisms underlying these changes in the offspring following immune challenge.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…52 Our model is a pregnancy infection model, which was found to have increased plasma inflammatory factors, including TNF-α, after viral infection and it has been reported that TNF-α activates the NF-κB pathway, which affects EphB2 transcription, all three of which can be increased under injury or disease states. 84,85 In Opcml-deficient mice, which exhibit schizophrenic-like behaviors but reduced EphB2 expression, 54 we differ from previous studies, haps because we use a different The pathogenetic mechanisms of different diseases may lead to different changes in EphB2 receptor expression. One limitation of this study is that we did not obtain insight into the mechanisms underlying these changes in the offspring following immune challenge.…”
Section: Discussionmentioning
confidence: 84%
“…Using a model of depression in mice induced by chronic social defeat stress shows a decrease in EphB2 receptor protein levels and an associated susceptibility to stress 52 . Our model is a pregnancy infection model, which was found to have increased plasma inflammatory factors, including TNF‐α, after viral infection and it has been reported that TNF‐α activates the NF‐κB pathway, which affects EphB2 transcription, all three of which can be increased under injury or disease states 84,85 . In Opcml‐deficient mice, which exhibit schizophrenic‐like behaviors but reduced EphB2 expression, 54 we differ from previous studies, haps because we use a different model.…”
Section: Discussionmentioning
confidence: 93%
“…Recently, a detailed description of the EPHB2-RNF186-TAB2-TAK1 signaling cascade in CRC carcinogenesis has been described in detail ( 137 ). Upon tumor necrosis factor (TNF) stimulation, EphB2 undergoes ubiquitination mediated by the E3 ligase RNF186, resulting in the recruitment and phosphorylation of TAB2.…”
Section: Ephb Receptorsmentioning
confidence: 99%
“…The absence of RNF186 in CRC cells significantly reduces the malignant phenotype in a murine colitis model. Furthermore, a genetic mutation in EphB2 has been identified in a family with CRC, demonstrating a gain-of-function mutation that enhances TNF signaling activation ( 137 ).…”
Section: Ephb Receptorsmentioning
confidence: 99%
“…The literature review revealed that the vast majority of the identified genes had previously been linked to colorectal cancer pathogenesis. Of these genes, the ones that seem to have an important role in CRC are EZH2, PTEN, EGFR, IGF1, HGF, SMAD4 and PTGS2 [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 ].…”
Section: In Silico Analysis Of Crc Exosomal Lncrna/circrna–mirna–targ...mentioning
confidence: 99%